TRACE FOSSILS OF CAMBRIAN AGLASPIDID ARTHROPODS - Hesselbo, S (1988)
A new trace fossil, Raaschichnus gundersoni, from the Upper Cambrian St. Lawrence Formation of Wisconsin, was produced by an aglaspidid arthropod. The rusophyciform trace, which occurs singly and in series, is distintive in showing marks left by the tail-spine. Other trace fossils previously considered to have been made by aglaspidids were probably excavated by animals lacking a tail-spine and with appendage morphologies very different from the aglaspidids of Wisconsin. -Author Wisconsin appendages